2008
DOI: 10.1007/s11095-008-9635-y
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol 400 Enhances the Bioavailability of a BCS Class III Drug (Ranitidine) in Male Subjects but Not Females

Abstract: All doses of PEG 400 enhanced the bioavailability of ranitidine in male subjects but not females, with the most pronounced effect in males noted with the 0.75 g dose of PEG 400 (63% increase in bioavailability compared to control, p < 0.05). These findings have significant implications for the use of PEG 400 in drug development and also highlight the importance of gender studies in pharmacokinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 43 publications
2
58
0
1
Order By: Relevance
“…The low molecular weight PEGs (<600) are liquids in nature and commonly employed as a vehicle to enhance the solubility and bioavailability of poorly water-soluble drugs (29). However, recent studies have revealed that PEG 400 at the doses relevant to pharmaceutical formulations stimulates GI motility and accelerates small intestine transit, leading to lower drug bioavailability (15,16,20). Like sorbitol and mannitol, PEGs cannot be absorbed in the intestine and thus retains fluid by osmotic action.…”
Section: Polyethylene Glycolsmentioning
confidence: 99%
See 4 more Smart Citations
“…The low molecular weight PEGs (<600) are liquids in nature and commonly employed as a vehicle to enhance the solubility and bioavailability of poorly water-soluble drugs (29). However, recent studies have revealed that PEG 400 at the doses relevant to pharmaceutical formulations stimulates GI motility and accelerates small intestine transit, leading to lower drug bioavailability (15,16,20). Like sorbitol and mannitol, PEGs cannot be absorbed in the intestine and thus retains fluid by osmotic action.…”
Section: Polyethylene Glycolsmentioning
confidence: 99%
“…Additionally, PEGs have been demonstrated to interact with certain transporters, particularly efflux transporters such as Pglycoprotein (P-gp) (28). Table II provides the summary data of three bioavailability studies previously conducted on ranitidine with PEG 400 (15,16,20). In these studies, various amounts of PEG 400 were added to ranitidine solutions (in orange juice or water) and administered to healthy volunteers.…”
Section: Polyethylene Glycolsmentioning
confidence: 99%
See 3 more Smart Citations